1988
DOI: 10.1093/ajcn/47.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Body fat deposition in adult obese women. II Changes in fat distribution accompanying weight reduction.

Abstract: This study examined changes in body fat distribution in 68 women who lost an average of 12.3 kg from an initial weight of 103.6 kg. Weight reduction was accompanied by a small but statistically significant reduction of 1.2% in the waist-to-hip ratio, suggestive of a reduction in upper-body obesity. Subjects with greater upper-body obesity tended to achieve greater reductions in the waist-to-hip ratio. Changes in five circumference measures were highly correlated with losses of fat and showed that subjects with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 0 publications
4
13
1
Order By: Relevance
“…However, the greater change occurred in the deep adipose tissue, particularly the preperitoneal fat layer. Similar to the authors of previous studies, 3,32 we found that weight loss caused only a small decrease in the WHR because of simultaneous decreases in waist and hip circumferences. Accordingly, the WHR was not useful for quantifying the intra-abdominal fat loss.…”
Section: Discussionsupporting
confidence: 91%
“…However, the greater change occurred in the deep adipose tissue, particularly the preperitoneal fat layer. Similar to the authors of previous studies, 3,32 we found that weight loss caused only a small decrease in the WHR because of simultaneous decreases in waist and hip circumferences. Accordingly, the WHR was not useful for quantifying the intra-abdominal fat loss.…”
Section: Discussionsupporting
confidence: 91%
“…44 However, we found no evidence that the weight changes exhibited over the 3 years of the study were related to changes in WHR, despite the fact that the women had gained 5 lb on average and 24 of the 108 women had gained 10 lb or more. In contrast, we found that there were significant increases in both the waist and hip circumferences considered separately and that the changes in these circumference measures were related to weight 46 for example, studied 68 female participants in a weight control program after a weight loss of 12.3 kg. These women showed decreases in WHR, from 0.827 to 0.817.…”
Section: Change In Waist To Hip Ratio From Baseline To Final Follow-upmentioning
confidence: 81%
“…There is some evidence that weight change may alter WHR (Bjorntorp, 1985b;King and Katch, 1986;Himes, 1988;Tremblay et al, 1988;Wadden et al, 1988;Shimokata et al, 1989); consequently, estimates of risk based on WHRs in cross-sectional data must be validated in future rospective studies in American Indians.…”
Section: Resultsmentioning
confidence: 99%
“…The few available studies examinin BFD chan es with weight loss achieve cise, or both indicate that modification of BFD is possible (King and Katch, 1986;Tremblay et al, 1988). Additionally, there is some evidence that central fat deposits are particularly sensitive to weight loss, so that a more health BFD profile may result from nal (Bjorntor ,1985b;Himes, 1988;Wadden et al, 1988;{himokata et al, 1989). Amon Do ib Indians central BFD is associate probabl reflect dietary and activity patterns (izathmary and Holt, 1983;Szathmary et al, 1987).…”
Section: Resultsmentioning
confidence: 99%